Factors leading to anastomotic stricture after esophageal atresia operation [Özofagus atrezisi ameliyati sonrasi anastomoz darliǧi gelişimini etkileyen faktörler] - (:unkn) unknown (My University, 2003)
Aim: Anastomotic stricture (AS) is the most common postoperative complication in patients with esophageal atresia. This complication is reported between 17.7 and 50% in different series. In this paper we evaluated the factors that may lead to AS in the postoperative period of esophageal atresia and distal tracheoesophageal fistula (TEF) patients. Method: Sixty-eight patients were operated for esophageal atresia in our institute in a period of twelve years. Thirty-nine of these patients had a long-term follow-up. Thirty-four of these 39 patients had esophageal atresia (EA) with a distal TEF. Patients underwent early primary anastomosis. AS was dilated with esophageal balloon dilators under fluoroscopic control under general anaesthesia. Narrowing that required two or more dilations was defined as AS. The relationship between AS and the number of stitches used for the anastomosis, anastomotic leak (AL), gastroesophageal reflux (GER) and the gap between the two segments was evaluated. Results: AS developed in 13 of 34 patients. No significant relationship was found between the number of stitches for the anastomosis and AS. AS was detected in three of four patients with AL, but again no significant relationship could be find between AL and AS if the whole group was considered. Only a mild correlation was found between the gap between the esophageal segments and AS. If patients with AL were excluded a significant relationship between gastroesophageal reflux (GER) and AS was demonstrated. Conclusion: AS is a common postoperative complication in patients with esophageal atresia. Different factors may lead to development of AS. In our series we detected a significant relationship between GER and AS and a mild correlation between gap and AS.
Keywords: Anastomotic stricture; Esophageal atresia